Evaluación de la calidad educativa: situación y desafíos - Díaz Diaz, Hugo (2010)
Latín America has embarked on the implementation of evaluation polides -and Peru is not an exceptionto tackle students' underachievement in national and international evaluations that seeks to measure the student' learning process so as to improve public school education quality. The public opinion is in favor of the establishment of these mechanisms and,above all, of an evaluation culture.